Analysis of Operational Risk Management Literature in Islamic Banking - Okta Sari; Anggun Okta Fitri (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2025)
Operational risk will always be faced by all financial institutions in running their business and business, and it cannot be separated by human factors, services, administrative processes and so on. The purpose of this study to examine in depth how operational risk management is applied by Islamic banking, especially in Indonesia. This research method uses descriptive qualitative approach with literature review technique to analyze operational risk management in Islamic banking. A literature study was chosen as the method to answer the research question. Data is collected through online searches. The results showed that operational management is very important for the sustainability of Islamic banks in the future, in addition to the benefits that can be received indicate the contribution of good management can be minimized due to unwanted operational errors. Islamic banks from the literature analyzed, have not shown to have developed effective solutions to manage the risks of conventional banks and face their own unique risks.